State-Level Trucking Employment and the COVID-19 Pandemic in the U.S: Understanding Heterogenous Declines and Rebounds - Jonathan Phares; Jason W. Miller; Stephen V. Burks (Institute of Labor Economics (IZA), 2023)
Some of the U.S. states saw sharper declines in truck transportation payrolls at the onset of the COVID-19 shutdown, and others displayed differing trajectories in the rebound of truck transportation payrolls during the economic recovery. Analyzing why provides theoretical and practical insights regarding labor dynamics in the trucking sector. In this vein we extend factor market rivalry theory regarding labor dynamics in the trucking sector: we suggest that trucking firms have compound relations with demand generating sectors in that they may compete for the same workers. Sectors differ in how output changes affect both their demand for trucking freight and the extent of their labor poaching; this creates differing net effects on trucking employment. We create a state-level archival data set of truck transportation establishment payrolls from the Quarterly Census of Employment and Wages, which we combine with other archival sources. We test our hypotheses via discontinuous growth curve models estimated using the mixed effects modeling framework. Effects vary by time period and industry, but manufacturing and natural resource extraction stand out in perhaps surprising ways, and changes in demand for local freight movements are especially important. Our results align with our theory and have important implications for managers and policy makers.
Keywords: J21; L92; R41; 330; truck transportation; motor carrier; COVID-19; pandemic shutdown; pandemic recovery; trucking employment